2006
DOI: 10.1258/004947506778604652
|View full text |Cite
|
Sign up to set email alerts
|

Gynaecologic mortality in Enugu, Nigeria

Abstract: A retrospective review of 79 deaths in 2033 gynaecologic admissions at a referral centre showed that the leading causes of mortality were cervical cancer, choriocarcinoma, septic abortion and ovarian cancer, in that order. The results suggest a need for an organized cancer programme to limit morbidity and mortality from malignant disease of the female genital tract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 3 publications
0
13
0
Order By: Relevance
“…This agrees with results of previous studies from this center. [1114] The pattern of genital tract malignancy in this study differs from the pattern in developed countries, where ovarian cancer has taken the leading position mainly due to the effects of screening and treatment of premalignant lesions of the cervix which has lead to a dramatic decrease in the incidence of cervical cancers. [15] The number 1 position of carcinoma of the cervix in this study indicates that the effect of cervical cancer screening and treatment of premalignant lesions of the cervix may not be obtainable in Nigeria.…”
Section: Discussionmentioning
confidence: 96%
“…This agrees with results of previous studies from this center. [1114] The pattern of genital tract malignancy in this study differs from the pattern in developed countries, where ovarian cancer has taken the leading position mainly due to the effects of screening and treatment of premalignant lesions of the cervix which has lead to a dramatic decrease in the incidence of cervical cancers. [15] The number 1 position of carcinoma of the cervix in this study indicates that the effect of cervical cancer screening and treatment of premalignant lesions of the cervix may not be obtainable in Nigeria.…”
Section: Discussionmentioning
confidence: 96%
“…This is consistent with a previous audit of gynecological cancers in this center three decades ago and as well as the findings of a more recent report. [617] Similarly, studies across Nigeria showed that 43-62 cases of ovarian cancer would be expected to be seen in about 10 years. [7891011] These underlie the rarity of ovarian cancer in Nigeria.…”
Section: Discussionmentioning
confidence: 99%
“…[4] In Enugu, ovarian cancer has been found to be the fourth commonest cause of gynecological mortality. [6] Previous studies done in Nigeria showed that ovarian cancer constituted 7-22% of all gynecological malignancies. [7891011] Epithelial ovarian cancer is the commonest type of ovarian cancer and is known to be a disease of postmenopausal women.…”
Section: Introductionmentioning
confidence: 99%
“…Gynecological cancers have been shown to contribute overwhelmingly to gynecological mortality in our environment 9. However, we found scanty literature on the management of these cancers.…”
Section: Introductionmentioning
confidence: 91%